SUSTENANCE IN MARRIAGE FROM THE PERSPECTIVE OF SUFI INTERPRETATION - Sulha Khoridatun Nafisah (STAI Nusantara Kota Banda Aceh, 2026)
This research is motivated by people's belief that marriage can open the door to sustenance and bring blessings in life. However, this understanding needs to be studied more deeply through the perspective of tafsir and Sufism. This research aims to examine the interpretation of the verses of sustenance in the context of marriage according to al-Ālūsī in the book of tafsir Rūḥ al-Ma'ānī and its relevance to the theory of Sufism of Imam al-Gazālī. In contrast to previous research that discussed the concept of sustenance and marriage in general, this study specifically highlights the verses of sustenance in marriage from a sufistic perspective. This research uses a descriptive-analytical method with a qualitative approach based on library research and thematic methods (mauḍū'ī). The data were analyzed descriptively and analytically through the approach of al-Gazālī Sufism. The primary source of data for this study is the book of tafsir Rūḥ al-Ma'ānī by al-Ālūsī with a focus on QS. al-An'ām [6]: 151, QS. al-Nūr [24]: 32, QS. al-Naḥl [16]: 72, QS. al-Aḥzāb [33]: 31, and QS. al-Ṭalāq [65]: 3. The results of the study show that al-Ālūsī not only explains the external meaning of the verse, but also the inner dimension in the form of tawakal, riḍa, and belief in the guarantee of sustenance from Allah for married couples. This thought is relevant to the concept of al-Gazālī Sufism which emphasizes the purification of the soul and spiritual dependence on Allah in obtaining sustenance.